Cooperation and the evolution of hunter-gatherer storytelling - Daniel Smith (Nature Portfolio, 2017)
Storytelling entails costs in terms of time and effort, yet it is a ubiquitous feature of human society. Here, Smith et al. show benefits of storytelling in Agta hunter-gatherer communities, as storytellers have higher reproductive success and storytelling is associated with higher cooperation in the group.